VALIDITAS BAHAN AJAR E-MODUL PADA MATA KULIAH MATEMATIKA TERAPAN PADA MAHASISWA - Halik, Fitriani; Bonitalia; Suardi; Saiful, Nur; Sulaiman, Najmawati (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
This research is a type of research and development that aims to determine the validity of e-module teaching materials in applied mathematics courses for students. This research includes referring to the 4D development model which consists of several phases, namely the stages of defining, designing, developing, and disseminating. The product developed is in the form of e-module teaching materials in applied mathematics courses. The test subjects in this study were graphic engineering students at the State Polytechnic of Creative Media Makassar. The instrument used in this study was a validation sheet consisting of two validators from design experts and materials experts. Based on the results of the research that has been done, an analysis of the validation results: (1) graphic validity, namely 4.7 is in the very valid category; (2) language validity, which is 4.9, is in the very valid category; (3) construct validity is 4.9 is in the very valid category; and (4) e-module presentation that is 4.7, is in the very valid category so that the average value of all aspects is 4.8 which is in the very valid category. So that it can mean that the e-module teaching materials in applied mathematics courses that have been developed are declared valid to be used as teaching materials in the learning process.